Transgenic GDNF Positively Influences Proliferation, Differentiation, Maturation and Survival of Motor Neurons Produced from Mouse Embryonic Stem Cells - Cortés, Daniel; Robledo-Arratia, Yolanda; Hernández-Martínez, Ricardo; Escobedo-Ávila, Itzel; Bargas, José; Velasco, Iván (Frontiers in Cellular Neuroscience, 2016)
Embryonic stem cells (ESC) are pluripotent and thus can differentiate into every cell type present in the body. Directed differentiation into motor neurons has been described for pluripotent cells. Although neurotrophic factors promote neuronal survival, their role in neuronal commitment is elusive. Here, we developed double-transgenic lines of mouse ESC that constitutively produce Glial cell-derived neurotrophic factor (GDNF) and also contain a GFP reporter, driven by HB9, which is expressed only by postmitotic motor neurons. After lentiviral transduction, ESC lines integrated and expressed the human GDNF gene without altering pluripotency markers before differentiation. Further, GDNF-ESC showed significantly higher spontaneous release of this neurotrophin to the medium, when compared to controls. To study motor neuron induction, control and GDNF cell lines were grown as embryoid bodies and stimulated with retinoic acid and Sonic Hedgehog. In GDNF-overexpressing cells, a significant increase of proliferative Olig2+ precursors, which are specified as spinal motor neurons, was found. Accordingly, GDNF increases the yield of cells with the pan motor neuronal markers HB9, monitored by GFP expression, and Isl1. At terminal differentiation, almost all differentiated neurons express phenotypic markers of motor neurons in GDNF cultures, with lower proportions in control cells. To test if the effects of GDNF were present at early differentiation stages, exogenous recombinant human GDNF was added to control ESC, also resulting in enhanced motor neuron differentiation. This effect was abolished by the co-addition of neutralizing anti-GDNF antibodies, strongly suggesting that differentiating ESC are responsive to GDNF. Using the HB9::GFP reporter, motor neurons were selected for electrophysiological recordings. Motor neurons differentiated from GDNF-ESC, compared to control motor neurons, showed greater electrophysiological maturation, characterized by increased numbers of evoked action potentials, as well as by the appearance of rebound action potentials, sag inward rectification, spike frequency adaptation and spontaneous synaptic potentials. Upon challenge with kainate, GDNF-overexpressing cells are more resistant to excitotoxicity than control motor neurons. Together these data indicate that GDNF promotes proliferation of motor neuron-committed precursors, promotes neuronal differentiation, enhances maturation, and confers neuroprotection. GDNF-expressing ESC can be useful in studies of development and disease.